Characteristics and distribution of respiratory therapy practitioners in Saudi Arabia: national cross-sectional results - Hajed M. Al-Otaibi (Human Resources for Health)
Abstract Background Respiratory therapy services commenced in Saudi Arabia (SA) in the mid-1970s. Since then, respiratory therapists have become integral members of the healthcare team. However, data about the characteristics and distribution of the respiratory therapy workforce in SA are limited. Therefore, the primary objective of this investigation is to examine the characteristics and distribution of respiratory therapy practitioners in SA. Methods This is a cross-sectional study. Data were obtained from the Saudi Commission for Health Specialties (SCFHS) database as of January 10, 2024. This includes all registered respiratory therapy practitioners. The available data include age, gender, highest qualification, professional ranking, geographical distribution, and employment status of respiratory therapy practitioners. Results The SCFHS database reveals that there are 5462 respiratory therapy practitioners registered with SCFHS. Females constitute 48% of respiratory therapy practitioners, and 85% of the entire workforce is under the age of 40. A Bachelor of Science degree is the highest academic qualification for 90% of these practitioners, with 75% professionally classified as specialists. The geographical distribution of the respiratory therapy workforce is uneven, with approximately 65% located in two regions: Riyadh and the Eastern province. Employment within this field is high, with 92% of practitioners currently employed. Conclusion The respiratory therapy workforce is witnessing steady growth, with the majority of respiratory therapy practitioners possessing a bachelor’s degree and classified as specialists professionally. Importantly, there is a clear imbalance in the distribution of these professionals across regions in SA.